The Determinants of Customers’ Loyalities of Smartphone - Kencana, I Putu Eka N.; Suputra, Gede Satria (Jurnal Matematika, 2015)
This research aimed to study the effect of brand image, users’ expectation, and users’ satisfaction  as the determinants for users’ loyalties of Samsung Smartphone by applying Partial Least Square–Structural Equation Modeling (PLS-SEM) method. Data gathered from 100 Samsung smartphone users at Denpasar, Indonesia were collected using questionnaires with 5 Likert’s scales during February–May 2015.  The results showed users’ loyalties was significantly affected by image of Samsung and users’ expectation.  The path coefficients for these causal relationships were 0.533 and -0.230 respectively, demonstrated images’ effect very dominant in forming users’ loyalties.  In addition, products’ image significantly affect users’ satisfaction, but user’s satisfaction did not significantly affect users’ loyalties. The final model had Goodness-of-Fit (GoF) index as much as 0.495 shows the model was sufficient to use for elaborating the relationship between contracts.
Keywords: customers survey; PLS-SEM; smartphone; structural model